tìm x: 12x x-33=9x27
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
12x – 33 = 32.33
12x - 33 = 9.27
12x - 33 = 243
12x = 243 + 33
12x = 276
x = 276:12
x = 23
Vậy x = 23
![](https://rs.olm.vn/images/avt/0.png?1311)
\(12x-33=3^3.3^3\)
\(12x-33=729\)
\(12x=729+33\)
\(12x=762\)
\(x=762:12\)
\(x=63,5\)
\(12x-33=3^3.3^3\)
\(12x-33=3^6\)
\(12x-33=729\)
\(12x=762\)
\(x=63,5\)
vậy \(x=63,5\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
12x - 33 = 32 x 33
=> 12x - 33 = 35
=> 12x - 33 = 243
=> 12x = 276
=> x = 23
![](https://rs.olm.vn/images/avt/0.png?1311)
12x + 33 = 32 . 33
12x + 33 = 36
12x = 36 - 33
12x = 3
x = 0,25
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
12x - 33=32. 33
=> 12x -33 = 35=243
=>12x=243+33=276
=>x=276: 12
=>x=23
Vậy x= 23
![](https://rs.olm.vn/images/avt/0.png?1311)
a: =>x^3+2x^2-8x^2-16x+15x+30=0
=>(x+2)(x^2-8x+15)=0
=>(x+2)(x-3)(x-5)=0
=>\(x\in\left\{-2;3;5\right\}\)
b: =x^2-12x+36-3
=(x-6)^2-3>=-3
Dấu = xảy ra khi x=6
![](https://rs.olm.vn/images/avt/0.png?1311)
Tìm x:
a, 96 - 3 . ( x + 1 ) = 42
3 . ( x + 1 ) = 96 - 42
3 . ( x + 1 ) = 54
x + 1 = 54 : 3
x + 1 = 18
x = 18 -1
x = 17
b, 12x - 33 = 32.33
12x - 33 =9 . 27
12x - 33 = 243
12x = 243 + 33
12x = 276
x=276:12
x=23
a, 96 - 3 . ( x + 1 ) = 42
3 . ( x + 1 ) = 96 - 42
3 . ( x + 1 ) = 54
x + 1 = 54 : 3
x + 1 = 18
x = 18 - 1
x = 17
b, 12x - 33 = 32 . 33
12x - 33 = 9 . 27
12x - 33 = 243
12x = 243 + 33
12x = 276
x = 276 : 12
x = 23